Gênero e espaço público : uma perspectiva da apropriação de praças de Goiânia-GO - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The research aims to analyze the relationship of the subject, according to its gender, with the public spaces. In order to do so, we considered the physical and subjective factors that make the public space of male and female dominion, the power relations involved and its reflection in the architectural spatial production and if these characteristics are applicable to four important squares of the city of Goiânia/GO . The Civic, Tamandaré, Avião and Violeiros squares were selected for the analysis of how the characteristics of their physical spaces interfere in the gender relations that occur in them. The first part of the research conceptualizes the public spaces, the relations of power printed by the genre and the public space from the perspective of gender. The second part introduces the historical and social context of the city, the neighborhoods and the squares. The third part focuses on the empirical study of people's daily lives in these public spaces. The methodology used is quantitative in the analysis of the data obtained through the application of the questionnaires and qualitative in the participant and non-participant observation of the spaces. It was verified that the chosen squares presented different forms of appropriation by the genera and that the characteristics of the space, its surroundings and the diversity of uses that it makes possible, have a direct influence in this relation.
Keywords: Espaço público; Gênero; Goiânia; Praças públicas; Public space; Genre; Goiânia; Public squares; CIENCIAS HUMANAS::SOCIOLOGIA